2007
DOI: 10.1590/s0037-86822007000500003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasound findings before and after praziquantel treatment among Venezuelan schistosomiasis patients

Abstract: Abdominal ultrasound can be a useful tool for diagnosing periportal fibrosis related to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Qiu et al (2000) also supported the evidence that liver fibrosis due to S. japonicum could recover to a certain extent after praziquantel treatment. Ruiz-Guevara et al (2007) indicated that 3-5 years after praziquantel treatment among Venezuelan patients with S. mansoni infection, complete reversal of periportal lesions was observed in 28.2% of the cases and progression of the disease in 5.1%. Another research in Ethiopia also revealed the reversibility of schistosomal periportal fibrosis after praziquantel therapy (Berhe et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al (2000) also supported the evidence that liver fibrosis due to S. japonicum could recover to a certain extent after praziquantel treatment. Ruiz-Guevara et al (2007) indicated that 3-5 years after praziquantel treatment among Venezuelan patients with S. mansoni infection, complete reversal of periportal lesions was observed in 28.2% of the cases and progression of the disease in 5.1%. Another research in Ethiopia also revealed the reversibility of schistosomal periportal fibrosis after praziquantel therapy (Berhe et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Considered a simple, safe and low-cost method, after the advent of portable equipment, it has been of invaluable help in the screening of populations living in endemic areas and in field-based studies of the disease. Taken as a nearly ideal tool in the diagnosis and classification of schistosomiasis, it is now used as a surrogate for the gold-standard in the diagnosis of schistosomiasis-related liver fibrosis (Doehring-Schwerdtfeger et al 1989, Abdel-Wahab et al 1992, Richter et al 1992, Abdel-Wahab & Strickland 1993, pinto-Silva et al 1994, Richter 2000, Kariuki et al 2001, Cota et al 2006, Marinho et al 2006, Ruiz-Guevara et al 2007.…”
mentioning
confidence: 99%
“…WHO patterns B-D, representing patients with mild liver fibrosis, are not pathognomonic and can be difficult to differentiate from normal liver or other disease etiologies. 65 The interobserver agreement has been found to be low, especially for mild cases. 66 Without the US imaging experience needed to subcategorize these patients accurately, misdiagnosis of milder cases of intestinal schistosomiasis can easily occur.…”
Section: Other Infectious Diseases With Potential For Pocus Applicationmentioning
confidence: 97%